Peningkatan Mutu Biji Cokelat Dengan Sistem Pengeringan Otomatis Berbasis Internet of Things - Sindar, Anita; Nuraisana; Erwin Panggabean; Bella Saputri; Nadia Aulia (LPPM Universitas HKBP Nommensen, 2025)
The type of drying tool depends on the amount of production, availability of resources, and capital owned by farmers. Controlled drying can produce products with even quality and diminish the risk of disruption due to uncertain weather conditions. Automatic drying enables farmers to use various types of agricultural and plantation products, which require special drying equipment. Chocolate is a type of plant that is easy to grow and also provides high profits for farmers. After the harvest, farmers separate the cocoa beans to be dried in the sun. Drying relies on sunlight, it takes days to dry. To facilitate drying cocoa beans, farmers are introduced to automatic tools using sensors. The Internet of Things (IoT) works based on the type of sensor, the sensor reads the data and then works to produce temperature and heat that makes it easier to dry chocolate. This activity aims to produce maximum cocoa beans so that they can be sold at high prices.